2006
DOI: 10.1111/j.1600-6143.2006.01489.x
|View full text |Cite
|
Sign up to set email alerts
|

TLR Engagement Prevents Transplantation Tolerance

Abstract: In many experimental models, heart, pancreas and kidney allografts are accepted long-term following costimulation-targeting therapies, whereas skin, lung and intestine resist the induction of tolerance under the same regimens. We noted that a common feature of the resistant organs is their constant exposure to commensal microbes and hypothesized that these microorganisms may stimulate Toll-like receptors (TLRs), promote alloresponses and prevent tolerance induction. This hypothesis prompts the predictions that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
204
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 200 publications
(219 citation statements)
references
References 40 publications
11
204
2
Order By: Relevance
“…Additional studies have focused on the role of TLRs and inflammation in tolerance induction. Two groups have reported that long-term graft survival in a highly immunogenic, fully allogeneic skin transplant model can be achieve with costimulatory blockade if both host and recipient are MyD88 deficient (51,52). In one of these reports, Walker et al (51) provide evidence to support a model in which absence of MyD88 impairs DC production of IL-6, in turn rendering alloreactive T cells more susceptible to suppression by CD4 ϩ CD25 ϩ regulatory T cells (Tregs).…”
Section: Examining Prr Signaling In Allotransplantationmentioning
confidence: 81%
See 2 more Smart Citations
“…Additional studies have focused on the role of TLRs and inflammation in tolerance induction. Two groups have reported that long-term graft survival in a highly immunogenic, fully allogeneic skin transplant model can be achieve with costimulatory blockade if both host and recipient are MyD88 deficient (51,52). In one of these reports, Walker et al (51) provide evidence to support a model in which absence of MyD88 impairs DC production of IL-6, in turn rendering alloreactive T cells more susceptible to suppression by CD4 ϩ CD25 ϩ regulatory T cells (Tregs).…”
Section: Examining Prr Signaling In Allotransplantationmentioning
confidence: 81%
“…Conversely, other studies show that despite costimulatory receptor blockade, challenge with TLR agonists such as LPS and CpG DNA at the time of allotransplantation prevents tolerance induction (52,54). Using donor-specific transfusion and CD154 Ab with a one-time TLR agonist challenge, Thornley et al (54) found that blockade of skin graft tolerance induction by TLR stimulation was associated with prevention of alloreactive CD8 ϩ T cell apoptosis.…”
Section: Examining Prr Signaling In Allotransplantationmentioning
confidence: 99%
See 1 more Smart Citation
“…We and others have also shown that engagement of single TLRs, receptors that recognize molecular patterns expressed by viruses, fungi, parasites, and bacteria, is sufficient to prevent transplantation tolerance by anti-CD154 mAb (15)(16)(17). Conversely, elimination of the TLR adaptor MyD88 facilitated the induction of transplantation tolerance to skin allografts (15,17). Together, these experiments underscore the importance of the TLR/MyD88 pathway in the ability to prevent transplantation tolerance (18).…”
Section: Linical Data Support a Correlation Between Viral Infectionsmentioning
confidence: 83%
“…This is thought to occur via direct activation of cross-reacting alloreactive T cells by viral Ags (7,9) or upon bystander activation of allospecific T cells (9,12). We and others have also shown that engagement of single TLRs, receptors that recognize molecular patterns expressed by viruses, fungi, parasites, and bacteria, is sufficient to prevent transplantation tolerance by anti-CD154 mAb (15)(16)(17). Conversely, elimination of the TLR adaptor MyD88 facilitated the induction of transplantation tolerance to skin allografts (15,17).…”
Section: Linical Data Support a Correlation Between Viral Infectionsmentioning
confidence: 99%